The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.jhsa.2014.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Tendon Grafts for Distal Radioulnar Ligament Reconstruction and Report of a Modified Technique

Abstract: Purpose To investigate the graft length necessary to complete a distal radioulnar ligament reconstruction and assess the suitability of several tendon graft sources. Methods We measured the graft length needed to complete the distal radioulnar ligament reconstruction in 7 fresh-frozen cadaver specimens. The pure tendon lengths of 7 tendon graft sources were measured: palmaris longus, extensor indicis proprius, slips of extensor digiti minimi and abductor pollicis longus, and portions of flexor carpi ulnaris,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Rather than measure potential available tendon length, including its intramuscular portion, we agree with previous investigators (Ito et al., 2001; Jang et al., 2014; Milone et al., 2017) who chose to measure ‘pure tendon length’, as it is a reproducible method to identify usable tendon. The mean pure tendon length (12.2 SD 3.6 cm) observed in this study is similar to tendon lengths reported by investigators measuring the PL in this manner (average 11.7–13.1 cm) (Ito et al., 2001; Jang et al., 2014; Milone et al., 2017).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Rather than measure potential available tendon length, including its intramuscular portion, we agree with previous investigators (Ito et al., 2001; Jang et al., 2014; Milone et al., 2017) who chose to measure ‘pure tendon length’, as it is a reproducible method to identify usable tendon. The mean pure tendon length (12.2 SD 3.6 cm) observed in this study is similar to tendon lengths reported by investigators measuring the PL in this manner (average 11.7–13.1 cm) (Ito et al., 2001; Jang et al., 2014; Milone et al., 2017).…”
Section: Discussionsupporting
confidence: 82%
“…When the PL tendon was present, the tendon length and diameter was determined using the measurement tool on the LOGIQ E9 ultrasound system in the long axis and short axis planes, respectively. Consistent with previously published methodology, tendon length was measured to the musculotendinous junction and tendon diameter was assessed in the midportion of the tendon (Jang et al., 2014; Milone et al., 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, extra tendons from the dorsum of the hand are usually shorter than PL, and extra slips could be thinner, mainly those of the little finger. 7 For instance, Jang et al 20 reported average lengths as follows: PL (127 mm), EDM (112 mm), and extensor indicis proprius (100 mm).…”
Section: Discussionmentioning
confidence: 99%